Online Counseling to Improve Mental Health among Midwives - Tiara Diah Sosialita (Proyeksi: Jurnal Psikologi, 2019)
As one of vital agent in health services, midwives play a central role in promoting well-being of their patients, especially for women and the babies. Unfortunately, the fact that they have poor condition of mental health and well-being can affect their services to patients and also potentially cause their mental health status can be worsen if not handled properly. Based on literature review and prior research in this field, the extension of potential uses of internet has expanded at an astounding rate, that are related to or effected by developing technologies and online counseling has grown as a mental health services in the past 15 or so years.The aim of this research was to evaluate the effectiveness of online counseling to improve mental health used pretest-posttest control group design. Subjects answered the General Health Questionnaire (GHQ-12) and analyzed by t-test SPSS 20. Data analysis showed that there was significant difference between experimental and control group scores. Resulth proved that online counseling was effective to improve mental health. This finding also provide clearly articulated of online counseling that beginning to coalesce and numerous helpful resources to improving mental health of society.